Development of Ethnic Groups in Thailand Linked Open Data - Wirapong Chansanam, Kulthida Tuamsuk, Juthatip Chaikhambung (International Journal of Advanced Science and Technology, 2020)
This paper presents the improvement of Linked Data technology for generating and publishing the ethnic groups in Thailand information to outside. This paper proposes a complete explanation of the tasks to implement, which includes a listing of steps, tools that assist in accomplishing the task, a number of picks for conducting the task, and fantastic practices and suggestions. Additionally, this paper offers a pilot model on the technology and publication of Linked Open Data about ethnic groups in Thailand, following the reachable instruction, in which the ethnic groups in Thailand be the property of the Princess Maha Chakri Sirindhorn Anthropology Centre (SAC) have been created and dispensed as Linked Open Data.